Stealth magnetoliposomes based on calcium-substituted magnesium ferrite nanoparticles for curcumin transport and release - Cardoso, Beatriz D. (2020)
In this work, stealth (aqueous and solid) magnetoliposomes containing calcium-substituted magnesium ferrite nanoparticles, CaxMg1-xFe2O4 (with x = 0.25, 0.50, 0.75) were developed as nanocarriers for curcumin, following previously developed work [3]. Magnetic nanoparticles were synthesized by coprecipitation method and characterized on their colloidal stability and optical, magnetic and structural properties.